Assessment of Non-Methane Hydrocarbon Trends in Ambient Air of Tronoh, Perak, Malaysia - Ismail, Muhammad Zulhafiz (Universiti Teknologi PETRONAS, 2017)
Air pollution are primary and most dangerous pollutions because it was involving all the creature in the world including human and ecosystem. Non-Methane Hydrocarbon was the pollutants that highlighted in this research and was categorized as the precursor for the ozone formation when reacted with radical oxides. The main objective of the researches was to examine the trends of Non-Methane Hydrocarbon (NMHCs) in ambient air of Tronoh and to investigate the effect of meteorological conditions on the trends of NMHCs. The flyover in Tronoh has been chosen as the location of study area due to condition of flyover’s column. There are a few researched has been done involving the investigation of NMHCs concentration at the developed area in Malaysia such as Pulau Pinang and Klang Valley. For this project, the sampling time was conducted from 27 October 2017 until 18 November 2017 which are during 3 weekdays and weekends respectively. In the beginning, the sampling was conducted to obtain the peak period of concentration NMHCs. Then, continue to indicate the diverse of concentration between the three-different location at the study area.